Analisis Pesan Moral pada Lirik Lagu “You Never Know” Blackpink - Rif'ah Kamilah; Askurifa’i (UNISBA Press, 2024)
Abstract. Music and songs as a communication message can convey messages in the context of life. Song lyrics can have a variety of messages. It can contain messages about motivation, culture and morals. In this case, music is an effective communication tool for conveying positive moral messages. Blackpink's song is entitled You Never Know which was released in 2020 feels personal for many people, including the Blackpink members themselves. The aim of this research is to find out the meaning of signifiers in song lyrics You Never Know, the meaning of the sign (signified) in the lyrics of the song You Never Know, and to study the meaning of moral messages in song lyrics You Never Know. This research uses qualitative research methods with a semiotic approach Ferdinand de Saussure and using a constructivist paradigm. The data collection techniques used in this research are text analysis, observation, literature study and interviews. Testing the validity of the data in this research uses source triangulation or what is usually called data triangulation. The results of this research found that there is a moral message in the song